Avaliação global da coagulação com tromboelastometria em pacientes com sepse grave e choque séptico - Ivan Euclides Borges Saraiva (2016)
Sepsis is often complicated by coagulopathy. Conventional coagulation tests may be insufficient to completely evaluate patients with sepsis. Thromboelastometry provides a global assessment of clotting and could theoretically overcome the limitations of conventional coagulation tests. In this study we included 50 patients with severe sepsis and septic shock, median age 48.5 years, 58% male sex, 44% with hypertension, 20% with diabetes mellitus, 14% with previous myocardial infarction, and 14% with heart failure. APACHE II (Adult Physiology and Chronic Health Evaluation II) median score was 17, SOFA (Sequential Organ Failure Assessment) median score in the first day was 7. Overall mortality was 14% in 7 days and 28% in 28 days. Microbiological confirmation of sepsis was done in 34% of patients, with most common germs being Escherichia coli (10%), Acinetobacter baumannii (10%), and Enterococcus faecalis (8%). Disseminated intravascular coagulation (DIC) was present in the first day in 28.26% of patients. Thromboelastometric variable Clot Formation Time (CFT) in the first day was predictive of DIC with and area under the Receiver Operating Characteristics (ROC) curve of 0.71. Thromboelastometric variables Clotting Time (CT), CFT, alpha angle and Maximum Clot Firmness (MCF) showed hypocoagulability in 88%, 70%, 66%, and 30% respectively in the first study day. Increase in CT and CFT in the third day and increase in CT in the seventh day were associated with microbiological confirmation of sepsis (P < 0.01 for all). Increase in CFT in the first day was associated with both 7 day and 28 day mortality (p < 0.01 and p = 0.02 respectively). Increase in CT and CFT in the third day and increase in CT in the seventh day were associated with 28-day mortality (p < 0.01 for all). The area under the ROC curve for the predictive ability of CT in the third day for 28-day mortality was 0.77. Nevertheless, when patients were compared with respect to the presence or absence of hypocoagulability based on thromboelastometric variables, there was no significant increase in risk for death. In conclusion, patients with severe sepsis and septic shock showed a thromboelastometric profile predominantly hypocoagulable, and the changes in thromboelastometric variables were associated with mortality.